Project ALPHA (Advanced Learning Program in the Humanities and Arts) Language. A Study Unit Designed for Education of the Gifted in the Humanities and the Arts - Le Storti, Anthony J.; Montgomery County Intermediate Unit 23, Blue Bell, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The unit on language is designed for presentation to middle school, junior high, and senior high gifted students. Information on objectives, materials, and presentation guidelines is presented for eight lessons on the following topics: purposes and process of language, successful/unsuccessful communication, precise/imprecise communication, connotation, image and language style, and creativity in language. (CL)
Sponsoring Agency: Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC.
ERIC Note: For related information, see EC 131 307-312.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Skills; Creativity; Gifted; High Schools; Junior High Schools; Language; Language Arts; Language Enrichment; Language Skills; Language Styles; Learning Activities; Middle Schools; Project ALPHA; Guides, Classroom -- Teacher